The adventures of Huckleberry Finn - Twain, Mark (New York : Bantam Books, 1981)
The adventures of a boy traveling down the Mississippi River with an escaped
Keywords: Voyages and travels -- Fiction; Friendship -- Fiction; Slavery -- Fiction; Mississippi River -- Fiction; Missouri -- History -- 19th century -- Fiction